Influence of drying methods and packaging materials on seed quality and storability of watermelon (Citrullus lanatus (Thunb.) Matsum & Nakai) seeds - Kehinde, T. O.; Soneye, A. A.; Shittu, M. M; Samson, E. A.; Bolajoko, M. H.; Abdullah, A.; Adebisi, M. A.; Oloyede, A. M. (ADAN JOURNAL OF AGRICULTURE, 2026)
Watermelon is relished across the world because of its pulp that is thirst quenching and highly nutritious. The continuous supply of watermelon depends on the availability of quality seeds which is a function of seed quality during storage. This study investigated the effects of seed drying methods and storage containers on the physiological quality and storability of some watermelon varieties. The experiment was a 4 x 4 x 3 factorial experiment (4 varieties, 4 drying methods and 3 packaging materials) in a completely randomized design with 3 replications. The seeds of the four watermelon varieties (Sugar baby, Kaolak, Black diamond and Winter king) were sun dried, oven dried, air dried and dried with silica gel before storing in paper bag, polythene bag and plastic container. The seeds were stored for six months under ambient temperature (27.5°C, RH = 64.7%). The stored seeds were assessed for physiological attributes at 30-day intervals. Data collected were subjected to Analysis of Variance and means separated using Tukey’s HSD test at 5% probability level. PROBIT analysis was also carried out to estimate the storage life of the seeds. Significant differences were observed in the seed physiological quality traits examined in the watermelon seeds due to differences in variety, seed drying methods and storage containers. Black diamond seeds exhibited a high viability rate of 92.6 and 76% and seed germination index of 11.58 and 9.51 respectively, before and after storage. Sun drying and oven drying methods greatly reduced the rate at which the watermelon seeds deteriorated. Oven drying method reduced germination percentage of the watermelon seeds. The PROBIT result revealed that watermelon seeds deteriorated at different rate, irrespective of the packaging material in which it is been stored for a period of 180 days. The highest estimate of seed storage-life was obtained with sugar baby seeds that were sun dried then, stored in paper bag (132.7 days). The study concluded that sun drying method was identified as the best seed drying method for the watermelon varieties. Therefore, water melon seeds could be sun dried and then stored in either a paper or polythene bag for the attainment of good physiological quality and extended storability.